Influence Financial Management and Use Accounting Information Technology in the Preparation of BUMDes Financial Statements - Putri, Ani; Blongkod, Harun; Mahmud, Muliyani (Universitas Negeri Gorontalo, 2024)
Purpose: This study aimed to investigate how financial management and the utilization of accounting information technology influence the creation of financial results statements.Design/Methodology/Approach: This study utilized a quantitative methodology using a Likert scale questionnaire to collect primary data. A saturated sample or survey technique was used to obtain a sample of 27 BUMDes with a total of 202 respondents. Testing the research hypothesis using the AMOS 24 tool.Findings:The findings indicated that financial management lacked a beneficial and notable influence on the enhancement of BUMDes financial reporting. Conversely, the adoption of information related to accounting technology demonstrated a positive and noteworthy impact on the development of BUMDes financial reports. Furthermore, when considered together, both financial management and the adoption of accounting information technology exhibited a positive and noteworthy influence on the development of BUMDes financial reports, as elucidated by the 90.2% R-square value. In comparison, the remaining 9.8% was attributed to external variables beyond the scope of the study in Bone Bolango Regency, Gorontalo Province.